SIMULASI KARAKTERISTIK GENANGAN BANJIR MENGGUNAKAN HEC-RAS 5 (STUDI KASUS SUBSISTEM SEKANAK DI KOTA PALEMBANG) - Al Amin, M. Baitullah; Ulfah, Luthfiyyah; Haki, Helmi; Sarino, Sarino (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
This paper deals with the modelling and simulation of flood inundation characteristics i.e. boundaries, depths, and velocities within Sekanak Subsystem which is one of flood-prone areas in Palembang City, Indonesia. The area of subsystem being studied was about 11 km2 . The new hydrodynamic model, HEC-RAS 5.0 was used to simulate the flood flow regimes by integrating the one-dimensional and two-dimensional model, known as combined 1D/2D flow model. The geometry of drainage channel was used as 1D domain to simulate the flow routing along the channel based on certain boundary conditions i.e. 25-yrs flood discharge and tide level both in upstream and downstream. The 2D domain in the model was the geometry of area beside the channel. The flow of 1D and 2D domain were connected by lateral weir, so the water which overflowing from the channel could be routed within 2D areas. The result shows that the area of inundation during lowest tide level is about 3.43 km2 with the velocities and depths range between 0 â 1.18 m/s and 0 â 3.08 m respectively. Furthermore, for average tide level, the area of inundation increases to 3.54 km with the velocities and depths range between 0 â 1.30 m/s and 0 â 3.11 m respectively. The maximum potential of inundation during the highest tide level is about 4.46 km2 with the velocities and depths respectively range between 0 â 2.64 m/s and 0 â 3.40 m. Therefore, it can be concluded that almost half of subsystem area potentially being inundated (40.11%), so it requires appropriate flood control and management to reduce the risk.